2019
DOI: 10.1093/neuonc/noz029
|View full text |Cite
|
Sign up to set email alerts
|

TSPO-PET and diffusion-weighted MRI for imaging a mouse model of infiltrative human glioma

Abstract: TSPO-PET and diffusion-weighted MRI for imaging a mouse model of infiltrative human glioma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 40 publications
(22 reference statements)
0
28
0
Order By: Relevance
“…We and others showed that [ 18 F]DPA-714 supports the identification of unique TSPO-expressing regions of the TME 20 , 22 that may represent areas with immunosuppressive myeloid cells 23 and glioma infiltration 24 , 54 . In spite of these promising results, very few studies describe the suitability of TSPO-binding radioligands for the monitoring of therapy outcomes 55 , 56 and even fewer specific for [ 18 F]DPA-714 in glioma.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…We and others showed that [ 18 F]DPA-714 supports the identification of unique TSPO-expressing regions of the TME 20 , 22 that may represent areas with immunosuppressive myeloid cells 23 and glioma infiltration 24 , 54 . In spite of these promising results, very few studies describe the suitability of TSPO-binding radioligands for the monitoring of therapy outcomes 55 , 56 and even fewer specific for [ 18 F]DPA-714 in glioma.…”
Section: Discussionmentioning
confidence: 79%
“…Recent studies of TSPO-PET in conjunction with in-depth immunophenotyping suggested [ 18 F]DPA-714 to non-invasively image the degree and heterogeneity of the glioma-associated immunosuppressive tumor microenvironment (TME) in vivo 22 , 23 . In addition, [ 18 F]DPA-714 may reveal distinct areas of glioma activity 22 , 23 compared to other imaging biomarkers and may be superior over [ 18 F]FET in detection of glioma infiltration 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in almost all types of CNS pathologies, TSPO levels are increased, and in some psychiatric disorders, such as schizophrenia, the TSPO signal in PET is decreased [34]. Although TSPO ligands are widely used in molecular imaging in all sorts of CNS pathologies, little is known about the role of TSPO expression and neuroinflammation in glioblastoma patients and PET imaging with TSPO radioligands is not yet standard for the imaging of brain tumor patients [18,19,[35][36][37]. In this study, we could show that the expression of TSPO is higher in brain tumor samples compared to those from epilepsy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its presence has been described also in tumors, increased levels of TSPO are associated with the presence of clusters of microglial/macrophage cells with an activated phenotype (23). For this reason, TSPO ligands, including [ 18 F]VC701 are used to image the inflammatory reaction present during tumor development and the relative modulation induced by drugs (24,25). Finally, to investigate therapy effects on tumor proliferation and inflammation markers, Ki67 and Iba1 were evaluated post mortem by immunohistochemistry (IHC).…”
Section: Introductionmentioning
confidence: 99%